(untitled) (Jurnal Bahasa, 2011)
The impetus of this study is driven from lack of previous research in pragmatic competence of Malaysian teenagers. Three hundred Form Four students in Peninsular Malaysia were randomly chosen in these zones: Central Zone (Negeri Sembilan), Eastern Zone (Kelantan), and Northern Zone (Kedah). The participants were requested to complete a questionnaire and sit for a written test. As grammar was the main focus, the study covered two parts: sentence construction skill "bermuka-muka and terkemuka", and proverb application skill "berat mata memandang, berat lagi bahu memikul". The findings revealed the respondents poor competence in questions relating to pragmatics. On the whole, the pragmatic competence is quite unsatisfactory (with 50-69 percent correct answers) for "berat mata memandang, berat lagi bahu memikul, bermuka-muka" and "terkemuka".